Social Media Use and Sexual Risk Reduction Behavior Among Minority Youth: Seeking Safe Sex Information. Issue 5 (September 2017) - Stevens, Robin; Gilliard-Matthews, Stacia; Dunaev, Jamie; Todhunter-Reid, Abigail; Brawner, Bridgette; Stewart, Jennifer
Abstract : Background: Sexual health is an important area of study—particularly for minority youth and youth living in disadvantaged neighborhoods. Objectives: The purpose of the research was to examine the sources of sexual health information associated with youth adopting sexual risk reduction behaviors. Methods: Data collection took place in a small city in the Northeastern United States using cross-sectional behavioral surveys and modified venue-based sampling. Participants included 249 African American and Latino youth aged 13–24. Participants reported their sources of information about contraception and human immunodeficiency virus/sexually transmitted disease, such as TV/movies, parents, social media; their intentions to have sex; and condom and contraception use during their last sexual activity. Social media use, past pregnancy experience, past sexual history, age, and gender were also measured. Standard tests of bivariate association (chi-square and F tests) were used to examine initial associations between sexual risk reduction behavior and exposure to sexual risk reduction information on social media. Logistic regression models were used to test multivariate relationships between information sources and sexual risk reduction behavior. Results: Youth who were exposed to sexual health messages on social media were 2.69 times ( p < .05) and 2.49 times ( p < .08) more likely to have used contraception or a condom at last intercourse, respectively. Parents, schools, or traditional media as information sources were not significantly associated with contractive use or condom use at last intercourse. Discussion: Youth sexual behavior is increasingly informed by social media messages. Health practitioners should utilize social media as an important health promotion tool.